PENGOTAKAN PERAN SEBAGAI STRATEGI SISTEM POLA BARU PADA PELAKU BISNIS MEDIA SOSIAL - Widiana Latifah; Roefaidah Harijati; Yulianti Yulianti (Jurnal Soshum Insentif, 2022)
Abstract - This study discusses the division of the roles of sellers and buyers in business on social media. The results show that the division of roles forms a management framework as a relatively new pattern as a business strategy in Social Media. The strategy through this new pattern system shows that there are three types of products offered by sellers to buyers which include products, services, and performance. The marketing strategy consists of two models, the first is the Tool Selling Line and long-term sustainable prospective buyers, the second is the Direct Line, namely without going through the tool. The research method applied is Research and Development, which analyzes a method and concept of marketing media, namely Social Media through a System framework with unique characteristics and is classified as a new pattern. Data sources include literature, documentation, visual media, audio visual, and social media. The results of the research are that there is a comprehensive model of connectivity and variations between sellers and buyers, line styles, seller strategies, benefits that buyers can feel directly. The implications of this research can be used as the basis for further research on business studies through social media, which are special, can be used by real business people in developing their business to social media, as additional knowledge for buyers about the nature and purpose if the buyer follows the application flow provided by the seller in connect. Abstrak - Penelitian ini membahas pembagian peran seller dan buyer dalam bisnis di Media Sosial. Hasil penelitian menunjukkan bahwa pembagian peran tersebut membentuk kerangka manajemen sebagai pola yang tergolong baru sebagai suatu strategi bisnis di Media Sosial. Strategi melalui Sistem pola baru ini menunjukan ada tiga jenis produk yang ditawarkan seller ke buyer yang meliputi produk, jasa, dan perform. Strategi memasarkannya terdiri atas dua model, pertama yaitu Tool Selling Line serta prospektif buyer berkelanjutan dalam jangka panjang, kedua adalah Direct Line yaitu tanpa melalui Tool. Metode penelitian yang diterapkan adalah Riset and Development yakni menganalisis suatu metode dan konsep media pemasaran yaitu Media Sosial melalui kerangka Sistem dengan ciri ciri yang unik dan tergolong sebagai pola baru. Sumber data meliputi literatur, dokumentasi, media visual, audio visual, dan media sosial. Hasil penelitian yaitu terdapat komprehensif tentang model koneksitas dan variasi antara seller dengan buyer, corak line, strategi seller, kemanfaatan yang dapat dirasakan buyer secara langsung. Implikasi penelitian ini dapat dijadikan dasar penelitian lebih lanjut tentang kajian berbisnis melalui Media Sosial bersifat khusus,dapat dimanfaatkan oleh pelaku bisnis riil dalam mengembangkan bisnisnya ke Media Sosial, sebagai tambahan pengetahuan bagi buyer tentang hakekat dan tujuan bila buyer mengikuti alur aplikasi yang disediakan oleh seller dalam berkoneksi.